Clostridium difficile infection and antibiotic-associated diarrhoea. - Mullish,BH; Williams,HRT (Clinical Medicine, 2018)
Antibiotic-associated diarrhoea is amongst the most common adverse events related to antibiotic use. Most cases are mild, but Clostridium difficile infection causes a spectrum of disease ranging from occasional diarrhoea to colitis, toxic megacolon, and potentially death. Recent developments in our understanding of the biology of the gut microbiota have given new insights into the pathogenesis of these conditions, as well as revealing a role for manipulation of the gut microbiota as a novel therapeutic approach. This CME review will give an overview of assessment of these conditions, before particularly focusing on the rapidly-developing area of their treatment.